GOVERNING MUSLIMS IN NON-ARABIC PERIPHERIES: COMPARATIVE ANALYSIS OF TURKEY, RUSSIA, INDIA, AND CHINA - K. Matsuzato (Сравнительная политика)
The article analyzes the forms of governing Muslims in Turkey, Russia, India, and China. The author considers historical background and current state of affairs in this sphere, similarities and differences of the four mentioned states in relations with the Muslim minorities.